A Study on the Complex Formation of Poly(Methyl Methacrylate), Poly(Vinyl Chloride) and Their Blend with Lithium Perchlorate Using FTIR Spectroscopy. Issue 1 (19th August 2020) - Ranjana, Patil Anitha Bhimarao; Sundaresan, B.
Abstract: Fourier transform infrared spectrum of the polymer‐salt complexes of poly(methyl methacrylate), poly(vinyl chloride), and the salt lithium perchlorate is analyzed for different compositions. The functional group analysis reveals that polymers PMMA and PVC form stable complexes with LiClO4 . A systematic analysis of the FTIR spectrum of the polymer blend‐salt complexes brings out the inference that the system with equal composition of PMMA and PVC, 37.5 wt% each, is found to show a better complex formation with 25 wt% of LiClO4 . The peak positional change of C═O group of PMMA is analyzed critically to identify the complex‐forming behavior of polymer blend.